Pharmacological compositions comprising glucokinase inhibitor for treating or preventing of glycogen storage disease - KIM DA SOHM; NAMKUNG WAN; PARK MIN SOO; SHIM JAE YONG; LEE JANG IK; JEON DONG KYU (2019)
The present invention relates to a pharmaceutical composition for preventing and treating glycogen storage disease comprising a glucokinase inhibitor as an active component. A galcinolic acid as the glucokinase inhibitor of the present invention can effectively inhibit glucokinase even at a very low concentration. In addition, the galcinolic acid inhibits excessive glycogen accumulation in a liver and has a hepatomegaly alleviation effect, thereby being expected to be widely used in medical fields as a therapeutic agent, an auxiliary agent, or a symptom relaxant of glycogen storage disease. 본 발명은 글루코키나아제 저해제를 유효성분으로 포함하는 당원병 예방 및 치료용 약학조성물에 관한 것이다. 본 발명의 글루코키나아제 저해제로서의 갈시놀릭산은 매우 적은 농도로도 효과적으로 글루코키나아제를 저해할 수 있다. 또한 간에서 과도한 글리코겐의 축적을 억제하고 간비대 등의 완화 효과가 있으므로, 당원병의 치료제, 보조적 치료제, 또는 증상 완화제로서 의학 분야에서 크게 이용될 것으로 기대된다.